(untitled) (Proceedings of International Conference on Special Education, 2015)
Attitudes that society takes towards people with visual impairment are a key factor affecting the implementation of inclusive education and the realisation of social integration of this group. This study surveyed 1,446 teachers, parents and students of 27 regular primary and secondary schools in 9 provinces of eastern, central and western China. The results show that their attitudes towards people with visual impairment are relatively positive, but mostly out of sympathy; at the same time, they demonstrate cognitive prejudice towards the abilities of people with visual impairment. This article further analyzes the potential effects that such attitudes have on the implementation of inclusive education.